2008
DOI: 10.1111/j.1460-2695.2008.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factors and crack opening displacements for slanted axial through‐wall cracks in pressurized pipes

Abstract: A B S T R A C T This paper proposes elastic stress intensity factors and crack opening displacements(CODs) for a slanted axial through-wall cracked cylinder under an internal pressure based on detailed three-dimensional (3D) elastic finite element (FE) analyses. The FE model and analysis procedure were validated against existing solutions for both elastic stress intensity factor and COD of an idealized axial through-wall cracked cylinder. To cover a practical range, four different values of the ratio of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Table 1 presents the J integral obtained by the proposed approach for different crack lengths. The results are in good agreement with the reference solutions [61] and analytical solutions reported in [62,63].…”
Section: Pressurized Cylindrical Shell With An Axial Cracksupporting
confidence: 90%
“…Table 1 presents the J integral obtained by the proposed approach for different crack lengths. The results are in good agreement with the reference solutions [61] and analytical solutions reported in [62,63].…”
Section: Pressurized Cylindrical Shell With An Axial Cracksupporting
confidence: 90%
“…The numbers of nodes and elements in a typical FE mesh are approximately 80,978 and 9360, respectively. Although, there is some curvature along the crack front that is resulting from the cylindrical transformation of a straight crack front in a plate, it has been reported that this technique does not affect the calculation of the results [18,19]. As shown in Fig.…”
Section: Fe Analyses Based On the R-o Idealizationmentioning
confidence: 96%
“…elastic stress intensity factors, elastic-plastic J-integrals and CODs, used for predicting crack growth behavior due to fatigue or primary water stress corrosion cracking (PWSCC), instability and leak rate [16][17][18][19][20][21]. For instance, Huh and Shim [18,19] have proposed the elastic stress intensity factor and COD solutions for a plate and a pipe by performing 3-dimensional (3-D) elastic FE analyses as tabular solutions. Also, Yellowes et al [20] presented the distributions of J-integral along the crack front based on limit FE analyses for a plate with a NiTWC.…”
Section: Introductionmentioning
confidence: 98%
“…Fatigue life prediction taking into account the effect of residual stress distribution by SIFs, has been proposed by Bahloul et al [9] who developed an improved calculation model. The finite element model for the calculation of elastic stress intensity factors and crack opening displacements in a cracked cylinder through the inclined axial wall subjected to internal pressure has been used by Huh et al [10]. This model and the analysis procedure have been validated against existing solutions.…”
Section: Introductionmentioning
confidence: 99%